Unlocking the Rich Potential of a Soft Gel-Cream Enriched with Royal Jelly for Topical Use - Monica-Elisabeta Maxim; Raluca-Marieta Toma; Ludmila Aricov; Anca-Ruxandra Leonties; Aurica Precupas; Rodica Tatia; Elena Iulia Oprita (Gels)
For decades, royal jelly achieved notoriety and became an ultra-rich ingredient with numerous pharmacological properties especially for its use in production of topical ointments and creams. A novel formulation enriched with 2% royal jelly has been developed and characterized. Rheological results highlight a gel-like behavior of the product in the packaging, as it does not flow from the costumer’s hand after application and behaves like a liquid, spreading evenly onto clean skin. A clear comparison in size distribution of pure and cream samples was noticed by dynamic light scattering analysis and completed further by Fourier transform infrared spectroscopy (FTIR-ATR) which showed off shift changes in the gel sample as compared to pure compounds. MTT assays were conducted in quintuplicate on murine fibroblasts cell line (NCTC L-929) for testing the biocompatibility of the product in the range of 50–1000 μg/mL over 24, 48 and 72 h. The designed formulation is typically intended to deliver active compounds to the skin surface and potentially into deeper layers. A molecular docking study was performed for binding mode prediction of P-gp protein residues with two ligands, quercetin and myricetin, in order to investigate their role in the internal modulation of drug transport across cell membranes within the skin.